Determinants of investor expectations and satisfaction: A study with financial professionals - Rene Schwaiger; Michael Kirchler; Florian Lindner; Utz Weitzel (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2018)
We investigate determinants of price expectations and satisfaction levels of financial professionals and students. In experiments with 150 professionals and 576 students, we systematically vary price paths according to the final return (positive or negative) and the way the final return is achieved (upswing followed by downswing or vice versa). Professionals show the most optimistic price expectations and are most satisfied if assets fall in price first and then recover. In addition, professionals' price expectations are highest after positive returns. Among students, qualitatively similar patterns emerge, but professionals' price expectations are less prone to framing effects.
Keywords: G02; G11; D03; C93; 330; Investor satisfaction; price expectations; financial professionals; experimental finance; investor behavior